The impact of the war in Yemen on US-Saudi relations in 2014-2017 - Roman Fedorovich Vinogradov; Mikhail Mikhailovich Shumilov (Управленческое консультирование, 2018)
The article reveals the contemporary state of Saudi-U. S. relations with reference to the growing tensions in the Middle East region, mainly Yemeni civil war. The focus is on American authorities’ response to an ineffective and bloody military campaign in Yemen led by Saudi Arabia and coalition forces. In the meantime, the article reveals the background and main causes of the civil war. Authors hold thesis on the fact that initial support of Saudi Arabia by the United States was driven by their aspiration to soften Saudi resentment towards nuclear deal with Iran. Authors also insist on the fact that since the end of 2016 more and more American politics declaim against the observance of the previously closed arms deal and condemn Saudi Arabia’s abusive fighting methods on the foreign territory. In attempts to explore scale, depth and perspective of the seeming split between the two countries authors take into account soundness of the bilateral relationships between U. S. and Saudi Arabia, huge interconnection of their economic interests and regional strategic priorities. In that context authors suggest the high probability of overcoming the existing discord in Saudi-U. S. relations under the new President of the United States - Donald Trump.